Performance Evaluation Standards for the Malay Gift Arrangement Skills Training Program at PKBM Insan Cendekia Pekanbaru - Nur Paziah; Rahmat Fahmi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to assess the performance of the Malay traditional gift-wrapping (hantaran) skills training program organized by PKBM Insan Cendekia, based on key performance indicators derived from the National Education Standards (SNP), specifically the process standard, graduate competency standard, and assessment standard. A mixed methods approach was employed with data triangulation through semi-structured interviews, participatory observation, and document analysis. Research subjects included the program manager and trainer. Results indicate that the program is highly effective: participant attendance reached 90%, competency test pass rate via the official Testing Center (TUK) was 60%, 80% of products were market-ready, and 40% of participants gained supplementary income. These findings support the relevance of nonformal education programs grounded in local cultural skills as instruments of sustainable community empowerment. Recommendations include improving financial documentation systems, intensive remedial sessions, and developing digital entrepreneurship modules.